2017 IEEE 85th Vehicular Technology Conference (VTC Spring) 2017
DOI: 10.1109/vtcspring.2017.8108471
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Rate Analysis for Massive MIMO-Enabled Heterogeneous Networks with Millimeter Wave Small Cells

Abstract: Abstract-The existing cellular networks are being modified under the umbrella of fifth generation (5G) networks to provide high data rates with optimum coverage. Current cellular systems operating in ultra high frequency (UHF) bands suffer from severe bandwidth congestion hence 5G enabling technologies such as millimeter wave (mmWave) networks focus on significantly higher data rates. In this paper, we explore the impact of coexistance of massive Multiple-Input Multiple-Output (MIMO) that provides large array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The probability of a user being associated to an NLoS small cell BS, given that a user is being served by the mmWave small cell tier is (19) where N (x) = x α N /α L , equality (a) follows from (32), and f N ( p(t))tdt} obtained by the following [9, Lemma 2], and…”
Section: B Mmwave Small Cell Tier Coveragementioning
confidence: 99%
“…The probability of a user being associated to an NLoS small cell BS, given that a user is being served by the mmWave small cell tier is (19) where N (x) = x α N /α L , equality (a) follows from (32), and f N ( p(t))tdt} obtained by the following [9, Lemma 2], and…”
Section: B Mmwave Small Cell Tier Coveragementioning
confidence: 99%
“…In this work, it is assumed that the legitimate user connects to the BS that provides maximum average received power [28]. Thus, the typical user located at the origin will connect to tier j only if…”
Section: B Downlink User Associationmentioning
confidence: 99%
“…In order to find the optimal SIR threshold that maximizes the ASE for the µWave tier, the optimization problem is stated as in (15), where the constraint insures higher data rate for wireless backhaul information than access information [23].…”
Section: ) µWave Tiermentioning
confidence: 99%
“…The results showed that the hybrid network achieved an average rate under coverage which is comparable to that of a mmWave network and much higher than the stand alone UHF network. In [15], the downlink performance in terms of coverage and rate of a three tier hybrid network where massive multiple input multiple output (MIMO) macro base stations (MBSs) are overlaid with small cells operating at either sub 6 GHz or mmWave bands was presented and the users were assumed to connect to any of the tier according to the association probability. It was observed that the implementation of massive MIMO on macro tier and deployment of high density of mmWave small cells led to the enhancement of rate and coverage.…”
Section: Introductionmentioning
confidence: 99%